2017
DOI: 10.1001/jamaophthalmol.2017.2553
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Related Functional Burden of Diabetic Retinopathy Across Severity Levels in the United States

Abstract: IMPORTANCE Among adults with diabetes in the United States, severe forms of diabetic retinopathy (DR) are significantly associated with a greater vision-related functional burden.OBJECTIVE To assess the functional burden of DR across severity levels in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 27 publications
3
64
0
1
Order By: Relevance
“… 34 The history of comorbid age-related ocular diseases, including cataract, glaucoma, and retinopathy, was based on the questionnaire and/or retinal images in accordance with previous studies. 35 , 36 , 37 Walking disability was defined by self-report of difficult walking or need of special equipment for walking. Self-rated health status was dichotomized as poor to fair or good to excellent.…”
Section: Methodsmentioning
confidence: 99%
“… 34 The history of comorbid age-related ocular diseases, including cataract, glaucoma, and retinopathy, was based on the questionnaire and/or retinal images in accordance with previous studies. 35 , 36 , 37 Walking disability was defined by self-report of difficult walking or need of special equipment for walking. Self-rated health status was dichotomized as poor to fair or good to excellent.…”
Section: Methodsmentioning
confidence: 99%
“…(13) A recent study on about one thousand subjects with diabetes showed that 25.4% of the patients had mild and moderate non-proliferative diabetic retinopathy, and 2.3% had severe non-proliferative diabetic retinopathy or proliferative diabetic retinopathy. (14) Another investigation in the United States indicated that out of 2240 youths with type 1 diabetes mellitus and 1768 youths with type 2 diabetes mellitus, 20.1% and 7.2% developed diabetic retinopathy over a median follow-up time of 3.2 and 3.1 years, respectively, showing that youths with types 1 or 2 diabetes mellitus are at a considerable risk for diabetic retinopathy and should undergo regular screenings. (15)…”
Section: United Statesmentioning
confidence: 99%
“…Diabetic retinopathy is one of the main microvascular complications of diabetes mellitus and can threaten the sight and progress to blindness [17,18] . National and international studies that have been conducted to determine the prevalence of diabetic retinopathy have reported values that range from 15% in some studies to 36% in others [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%